2004
DOI: 10.1152/ajpheart.01169.2003
|View full text |Cite
|
Sign up to set email alerts
|

Role of AT1 receptors and NAD(P)H oxidase in diabetes-aggravated ischemic brain injury

Abstract: jective of the present study was to examine the role of the angiotensin II type 1 receptor (AT1-R) in the diabetes-aggravated oxidative stress and brain injury observed in a rat model of combined diabetes and focal cerebral ischemia. Diabetes was induced by an injection of streptozotoxin (STZ; 55 mg/kg iv) at 8 wk of age. Two weeks after the induction of diabetes, some animals received continuous subcutaneous infusion of the AT1-R antagonist candesartan (0.5 mg ⅐ kg Ϫ1 ⅐ day Ϫ1 ) for 14 days. Focal cerebral is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
103
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 57 publications
5
103
0
1
Order By: Relevance
“…Ang II was found to activate p47phox via AT1 (30). In addition, ARB was reported to inhibit p22phox mRNA expression caused by mechanical stretching and in patients with diabetes mellitus (31,32). We also showed that AT1a deficiency in apoE-KO mice inhibited the expression of p22phox at 60 weeks of age.…”
mentioning
confidence: 61%
“…Ang II was found to activate p47phox via AT1 (30). In addition, ARB was reported to inhibit p22phox mRNA expression caused by mechanical stretching and in patients with diabetes mellitus (31,32). We also showed that AT1a deficiency in apoE-KO mice inhibited the expression of p22phox at 60 weeks of age.…”
mentioning
confidence: 61%
“…Support for this latter concept can be found in studies that have shown that stimulation of vascular cells with angiotensin II increases the activity of NAD(P)H oxidase, increases the expression of p47phox and stimulates the production of superoxide anion (Fukui et al, 1997;Griendling et al, 1994;Griendling et al, 2000;Landmesser et al, 2002;. Further, inhibition of AT1R can decrease angiotensin II-induced increases in superoxide anion production by vascular cells (Berry et al, 2000;Kusaka et al, 2004;Zimmerman et al, 2002). Thus, in the present study we tested the hypotheses that angiotensin II could impair eNOS-dependent reactivity of rat cerebral arterioles and that treatment of diabetic rats with an AT1R antagonist (losartan) would alleviate/prevent impaired eNOS-dependent responses of cerebral arterioles via an influence on oxidative stress.…”
Section: Introductionmentioning
confidence: 97%
“…NADPH oxidase-dependent production of superoxide radical (O 2 Ϫ ·) has been identified as a major contributor to oxidative injury in the brain under conditions of both inflammation and severe hypoxia/reperfusion injury (13)(14)(15)(16). Moreover, NADPH oxidase has been implicated in oxidative neurodegeneration, including Alzheimer's disease (17,18), and in dopaminergic neuronal injury in murine models of Parkinson's disease (19)(20)(21).…”
mentioning
confidence: 99%